Influence of Silybum Marianum on Morphine Addicted Rats, Biochemical Parameters and Molecular Simulation Studies on µ-Opioid Receptor - Malekshah, Rahime Eshaghi; Khaleghian, Ali (Drug Research, 2019)
The present study aimed to investigate effects of medicinal plant (Silybum marianum) on the animals with treatment of morphine addiction compared to chemical drug (Naloxane). Also, this study was conducted to evaluate the role of Silybum marianum on factors of serum ALT, AST activities and activity of the antioxidant enzyme:superoxide dismutase (SOD) as well as the extent of lipid peroxidation of Morphine addicted rats.High performance liquid chromatography (HPLC) has been used to measure Morphine in the serum, enzymes functions well as lipid peroxidation of Morphine addicted animals. Results demonstrate treatment with S. Marianum for opium rats at dose 400 mg/kg led to a major reduction in serum morphine compared to Naloxane (400 mg/kg>200 mg/kg>100 mg/kg>Naloxane. The positive effect of dose-dependence on liver enzymes function (ALT and AST) in order of 400 mg/kg>Naloxane>200 mg/kg>100 mg/kg. Furthermore, the findings show that the malondialdehyde levels are increased in opium-treated animals. However, the extracts also demonstrate a significant reduction in the MDA levels compared to the control, 400 mg/kg>200 mg/kg>Naloxane>100 mg/kg. Increase of Silybum marianum extract in rats pretreated significantly elevated the activities of superoxide dismutase (SOD).At last, our data suggest that Silibinin as the main component found in Milk thistle is more selective toward µ-Opioid Receptor than Morphine and Naloxane as a narcotic receptor antagonist.
Keywords: addiction; AST; ALT; TBA-MDA; SOD; hepatoprotectant; molecular docking.